Interrelations between logistics, trade, and law in the Incoterms® context: A bibliometric analysis of academic literature - Baena Rojas, José Jaime; López Cadavid, Diego Alejandro; Vanegas López, Juan Gabriel (Pomorstvo (Rijeka : 1999), 2024)
This study uses a comprehensive bibliometric analysis to examine the relationships between the International Commercial Terms (Incoterms®), logistics, and legal issues in the context of international trade. By examining a dataset of 290 documents published from 1973 to 2023 in various academic databases such as Web of Science, Google Scholar, Science Direct, among others, the research aims to identify trends, key issues, and potential future directions in this interdisciplinary field. The analysis reveals a significant increase in publications since 2010, with a focus on topics such as legal and contractual issues, supply chain management, risk mitigation, and the evolution of Incoterms® rules. Co-occurrence analysis emphasizes six distinct clusters, ranging from international trade dynamics and transaction costs to regulatory frameworks and risk management. The abstract content analysis further highlights the interconnectedness of legal, logistical and implementation issues. The study also identifies the United Kingdom, the United States, and South Korea as the most important countries contributing to the field. It is concluded that Incoterms® and its multidisciplinary essence generates a greater interest in the international trade, not only because of its incidence in diverse fields of management; but also, because these rules are updated to regulate better the business transactions. The findings provide valuable insights for researchers, policymakers, and practitioners, and show the importance of considering the multifaceted nature of Incoterms® research and its impact on global trade practices.